2012
DOI: 10.1371/journal.pone.0039672
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis Outbreak following Severe Flooding: A Rapid Assessment and Mass Prophylaxis Campaign; Guyana, January–February 2005

Abstract: Background Leptospirosis is a zoonosis usually transmitted through contact with water or soil contaminated with urine from infected animals. Severe flooding can put individuals at greater risk for contracting leptospirosis in endemic areas. Rapid testing for the disease and large-scale interventions are necessary to identify and control infection. We describe a leptospirosis outbreak following severe flooding and a mass chemoprophylaxis campaign in Guyana. Methodology/Principal Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 25 publications
1
54
0
1
Order By: Relevance
“…101 However, a time series analysis of diarrheal illness and flood water data from a health and demographic surveillance site found no support for a significant increase in diarrhea, including cholera, non-cholera, and rotavirus, in the three years following major flooding. 102 Two outbreaks of leptospirosis were confirmed within one month 103 and more than four weeks 104 after flooding, while approximately 27% of children presenting to a treatment facility with acute fever of unknown origin were diagnosed with leptospirosis within the first month after flooding. 105 Eye infections were seen in a significantly larger proportion of people living in flooded areas within four weeks of a flood compared to those living in non-flooded areas.…”
Section: Treatment Facility Presentations (%)mentioning
confidence: 99%
“…101 However, a time series analysis of diarrheal illness and flood water data from a health and demographic surveillance site found no support for a significant increase in diarrhea, including cholera, non-cholera, and rotavirus, in the three years following major flooding. 102 Two outbreaks of leptospirosis were confirmed within one month 103 and more than four weeks 104 after flooding, while approximately 27% of children presenting to a treatment facility with acute fever of unknown origin were diagnosed with leptospirosis within the first month after flooding. 105 Eye infections were seen in a significantly larger proportion of people living in flooded areas within four weeks of a flood compared to those living in non-flooded areas.…”
Section: Treatment Facility Presentations (%)mentioning
confidence: 99%
“…ReviewDoxycycline and penicillinThe role of antibiotics in chemoprophylaxis of leptospirosis is uncertain due to lack of large scale trials. More evidence based studies are required to generate evidence for antibiotics being used as chemoprophylaxis.Dechet [35]2012 PloS ONE Chemoprophylaxis campaign descriptionDoxycyclineThe effectiveness of the massive chemoprophylaxis campaign was inconclusive.McBride [57]2010 Pharmaceuticals ReviewDoxycyclineMay only act to reduce clinical illness rather than infection. May cause nausea and vomitingCruz [58]2009 Ethn.…”
Section: Table A1mentioning
confidence: 99%
“…Although previous studies have extensively reported the association of leptospirosis with heavy rainfall and consequent floods (Lau et al 2010b;Barcellos & Sabroza 2001;Gaynor et al 2007;Dechet et al 2012;Vanasco et al 2008;Mohan et al 2009), in this study we focused the analysis on not only rainfall but also other hydrological factors that might play an important role in the disease occurrence. For this, a total of five hydrologically-related covariates were developed to be tested within GWPR models.…”
Section: Hydrological Covariates Developmentmentioning
confidence: 99%
“…Outbreaks have been reported from many regions around the world, including: Italy, 1994, (Beniamino et al 1987) Nicaragua, 1995(Zaki & Shieh 1996, Brazil, 1996(Barcellos & Sabroza 2001, Russian Federation, 1997 (Kalashnikov et al 2003), Honduras, 1998(Naranjo et al 2008, India, 1997(Vijayachari et al 2003Sehgal et al 2002;Jena et al 2004), Australia, 1999(Smythe et al 2002) Hawaii, 2004(Gaynor et al 2007, Guyana, 2005(Dechet et al 2012, the U.S., 2005 (Stern et al 2010) and the Philippines, 2009 (Amilasan et al 2009). Besides being associated to floods following heavy rains during the rainy season, or floods which occur in areas affected by either tropical cyclones or land use/ land cover changes Mahajan & Chlabra 2008), outbreaks have been reported after occupational or recreational activities related to water such as fishing, farming, canoeing, fresh water swimming or bathing (Keith 1996;Sanders et al 1999;Sejvar et al 2003;Segura et al 2005;Vanasco et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation